BIOCHEMICAL FOUNDATIONS OF HEREDITARY DISEASES OF THE NERVOUS SYSTEM (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article discusses the causes and significance of hereditary diseases of the nervous system. It also discusses the most widely recognized neurological diseases in medicine and the conditions that accompany any disorder of the nervous system.